OP27 Patient-Reported Outcome Measures In Carotid Artery Revascularization. (12th January 2018) - Aber, Ahmed; Phillips, Patrick; Poku, Edith; Wood, Helen Buckley; Howard, Aoife; Palfreyman, Simon; Kaltenthaler, Eva; Jones, Georgina; Michaels, Jonathan; Essat, Munira
Abstract : INTRODUCTION: Patient-reported outcome measures (PROMs) provide a way to measure the impact of a disease and its associated treatments on the quality of life from the patients' perspective. The aim of this review was to identify PROMs that have been developed and/or validated in patients with carotid artery disease (CAD) undergoing revascularization, and to assess their psychometric properties and examine suitability for research and clinical use. METHODS: Eight electronic databases including MEDLINE and CINAHL were searched from inception to May 2015 and updated in the MEDLINE database to February 2017. A two-stage search approach was used to identify studies reporting the development and/or validation of relevant PROMs in patients with CAD undergoing revascularization. Supplementary citation searching and hand-searching reference lists of included studies were also undertaken. The Consensus-based standards for the selection of health measurement instruments (COSMIN) and Oxford criteria were used to assess the methodological quality of the included studies, and the psychometric properties of the PROMs were evaluated using established assessment criteria. RESULTS: Six PROMs, reported in five studies, were identified: 36-Item Short Form Health Survey (SF-36), Euro-QoL-5-Dimension Scale (EQ-5D), Hospital Anxiety and Depression Scale (HADS), Dizziness Handicap Inventory (DHI), Quality of life for CAD scale by Ivanova 2015 and a disease-specific PROM designed by Stolker 2010. The rigour of the psychometric assessment of the PROMs were variable with most only attempting to assess a single psychometric criterion. No study reported evidence on criterion validity and test-retest reliability. The overall psychometric evaluation of all included PROMs was rated as poor. CONCLUSIONS: This review highlighted a lack of evidence in validated PROMs used for patients undergoing carotid artery revascularization. As a result, the development and validation of a new PROM for this patient population is warranted in order to provide data which can supplement traditional clinical outcomes (stroke >30 days post-procedural, myocardial infarction and death), and capture changes in health status and quality of life in patients to help inform treatment decisions.